Staphylococcus aureus: a threat to food safety (Research, Society and Development, 2021)
Foodborne Diseases (FBD) affect millions of people worldwide. They are caused mainly by bacteria of the genus Staphylococcus, mainly Staphylococcus aureus. Among these, some produce enterotoxins that are resistant to high temperatures and can contaminate various types of foods such as milk and dairy products, in addition to meat products and others. For these reasons, it is necessary to study S aureus and Staphylococcal Enterotoxins (SE), which are the main causes of FBD, and the development of actions and new products that maintain the health of food, especially milk, daity dirivates and meat products, in order to reduce contamination. In addition to the study of more efficient techniques for detecting these contaminating agents. Among these techniques, molecular techniques stand out, which currently have been shown to be increasingly sensitive and specific. In general, the association of good hygiene practices and molecular detection techniques are fundamental for maintaining food health, avoiding losses in the industry and serious health problems.